Extracellular vesicles from human multipotent stromal cells protect against hearing loss after noise trauma in vivo. Issue 8 (21st December 2020) - Warnecke, Athanasia; Harre, Jennifer; Staecker, Hinrich; Prenzler, Nils; Strunk, Dirk; Couillard‐Despres, Sebastien; Romanelli, Pasquale; Hollerweger, Julia; Lassacher, Teresa; Auer, Daniela; Pachler, Karin; Wietzorrek, Georg; et al.
Abstract: The lack of approved anti‐inflammatory and neuroprotective therapies in otology has been acknowledged in the last decades and recent approaches are heralding a new era in the field. Extracellular vesicles (EVs) derived from human multipotent (mesenchymal) stromal cells (MSC) can be enriched in vesicular secretome fractions, which have been shown to exert effects (eg, neuroprotection and immunomodulation) of their parental cells. Hence, MSC‐derived EVs may serve as novel drug candidates for several inner ear diseases. Here, we provide first evidence of a strong neuroprotective potential of human stromal cell‐derived EVs on inner ear physiology. In vitro, MSC‐EV preparations exerted immunomodulatory activity on T cells and microglial cells. Moreover, local application of MSC‐EVs to the inner ear significantly attenuated hearing loss and protected auditory hair cells from noise‐induced trauma in vivo. Thus, EVs derived from the vesicular secretome of human MSC may represent a next‐generation biological drug that can exert protective therapeutic effects in a complex and nonregenerating organ like the inner ear. Abstract : The Effect of extracellular vesicles derived from human stromal cells on the inner ear has been investigated. The vesicles were characterized and tested in vitro in spiral ganglion neurons and in vivo in a mouse noise trauma model.